2020
DOI: 10.1016/j.matchemphys.2020.123479
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of single-walled carbon nanotubes in rich hydrogen/air flames

Abstract: Single-walled carbon nanotubes of an average diameter of 1 nm are produced in premixed laminar rich H 2 /air flames. • Temperatures and stoichiometries of the surrounding gases are key to successful CNT synthesis. • CNTs form as nanometre-thick fibrelets connecting the surrounding Fe 3 O 4 nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…As mentioned earlier, the abundance of oxygen assists in more heat release and creates a larger favorable environment for CNT production. Effect of abundance of high temperature region on improved yield and qualities of CNT has been observed by previous flame synthesis study by Zhang et al, [17]. Nonetheless, too much excess of oxygen is assumed to consume the potential carbon source or deactivate the catalyst particles and reduces CNT production.…”
Section: Effects Of Flame Structure On Cnt Growth Region At Varying Oxidizer Concentrationmentioning
confidence: 80%
See 1 more Smart Citation
“…As mentioned earlier, the abundance of oxygen assists in more heat release and creates a larger favorable environment for CNT production. Effect of abundance of high temperature region on improved yield and qualities of CNT has been observed by previous flame synthesis study by Zhang et al, [17]. Nonetheless, too much excess of oxygen is assumed to consume the potential carbon source or deactivate the catalyst particles and reduces CNT production.…”
Section: Effects Of Flame Structure On Cnt Growth Region At Varying Oxidizer Concentrationmentioning
confidence: 80%
“…A previous study pointed out that an increase in oxygen concentration provides more combustion and thus larger high temperature region [11]. In relation to this, Zhang et al, [17] mentioned that availability of abundant high temperature within the flame results in CNT with better quality and improved yield. However, a recent study demonstrated that there exists a limit to the oxygen concentration where too high of oxygen concentration can result in reduced CNT yield and growth rate [18].…”
Section: Introductionmentioning
confidence: 97%
“…[ 22 ]). For carbon nanomaterials, the most conventional method is chemical vapor deposition (CVD) [ 3 , 4 , 24 , 25 , 26 ], although there are other methods such as arc discharge and laser ablation [ 3 , 4 , 25 , 26 ]. Metal-oxide nanoparticles, including TiO 2 , SiO 2 , Fe x O y , and Al x O y , can be produced using the Stöber method [ 14 ] and precipitation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a premixed flat flame was utilized by Zhang et al [10] to synthesize single-walled CNT (SWCNT) in rich hydrogen/air combustion with a ferrocene catalyst.…”
Section: Introductionmentioning
confidence: 99%